Enhancing Soil Chemical Properties and Sweet Corn Growth by Solid Organic Amendments in Ultisol - Sri Mega Sianturi; Zainal Muktamar; Mohammad Chozin (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2019)
The negative impact of prolong and excessive application of synthetic fertilizers is a reason to reuse organic material as a plant nutrition resources and to enhance degraded soil. Organic materials such as animal and industrial wastes are commonly use as sources of organic amendment. The purpose of this study was to examine the changes in chemical properties of soil and the growth of sweet corn as affected by the application of solid organic fertilizers in Ultisol. This research was carried out in October 2016 until March 2017 at Greenhouse, University of Bengkulu, arranging in a Completely Randomized Design with two factors and three replications. The first factor was Organic amendment consisting of vermicompost, chicken manure, oil palm empty bunches compost (OPEBC). The second factors were rates of the amendment, i.e., 0, 10, 20, and 30 Mg ha-1. Results indicate that total soil organic carbon (TSOC) and total soil nitrogen (TSN) were not considerably different among types of organic amendments used in this study; however, an increase in soil pH and a decline of exchangeable Al are highest in the application of OPEBC as compared to others. Likewise, the growth of sweet corn was the best in soil amended with chicken manure. Soil chemical properties such as TSOC, TSN, soil pH significantly enhanced but exchangeable Al markedly lowered up to 20 Mg ha-1, then level off afterward. Sweet corn growth as indicated by plant height, shoot dry weight (SDW), and root dry weight (RDW) was also significant up to 20 Mg ha-1. This study suggests that the addition of organic amendment at a rate of 20 Mg ha-1 is sufficient to provide plant nutrient and improvement of soil properties for sweet corn growth.